Rapid in vitro microindexing of viroids in citrus - Kapari-Isaia, T.; Kyriakou, A. P.; Papayiannis, Lambros C.; Gregoriou, S.; Psaltis, I.; Tsaltas, Dimitrios (My University, 2008)
A new laboratory technique combining shoot-tip grafting in vitro and biological indexing on indicator plants was explored for the detection of citrus exocortis and related viroids. Three in vitro laboratory methods were used and compared with the classical biological method. With the classical in vivo method, diagnosis is based on the expression of symptoms on indicators 11-14 weeks after inoculation. In contrast, with the first in vitro method, microindexing in vitro of citron seedlings by graft inoculation, diagnosis was possible 12 days after inoculation; with the second method, microindexing in vitro of citron cuttings by graft inoculation, 20 days after inoculation; and with the third method, microindexing in vitro of citron cuttings by injection inoculation, 40 days after inoculation. Inoculated Etrog citron plantlets grown in vitro and tested by RT-PCR showed the same viroid content as the source plants. Of the three in vitro viroid indexing methods, microindexing on cuttings by grafting was easier and more reliable than microindexing either on seedlings or on cuttings by injection.
Keywords: Citrus exocortis disease; Citrus spp.; Detection and diagnosis; Etrog citron